INTEGRATING DEEP LEARNING IN CORRECTIVE FEEDBACK THROUGH DIGITAL COMICS TO INCREASE STUDENTS’ WRITING SKILLS - Misnawati; Munar; Irfani; Muhammad Reza (Universitas Muhammadiyah Makassar, 2026)
Writing is one of the most challenging skills for English as a Foreign Language (EFL) students, particularly in generating ideas, organizing paragraphs, and using accurate grammar and vocabulary. Effective corrective feedback is needed to help students improve their writing through meaningful revision. This study investigates the effectiveness of integrating deep learning into corrective feedback through digital comics to improve English as a Foreign Language (EFL) students’ writing skills. The objective of the research is to investigate whether corrective feedback designed to promote deep learning enhances students’ writing ability. In this study, deep learning is conceptualized as an active learning process in which students actively engage in understanding errors, reflecting on feedback, and revising their writing meaningfully. A quasi-experimental design was applied in this study. The subjects were tenth grade EFL students at Senior High School in Bireuen, Aceh. The students were assigned to an experimental group and a control group. Data were gathered using pre-test and post-test writing tests. Students’ writing skills were assessed in terms of content, organization, language use, vocabulary, and mechanics. The data were analyzed using descriptive statistics, effect size analysis, and normalized gain analysis. The findings indicated that students in the experimental group showed significant improvement in writing skills, with the average score from 58.0 on the pre-test to 78.4 on the post-test. The analysis indicated a large effect size with a Cohen’s d value of 2.05 and a moderate normalized gain score of 0.486. Improvement was found across all writing components, indicating deeper revision practices. This study contributes to EFL writing pedagogy by demonstrating how digital comics based corrective feedback can promote deeper reflection, meaningful revision, and improved writing instruction.